Foreign body intrusion monitoring and recognition approach in a power distribution room based on the improved YOLOv4 deep learning network - Chen, Shenyu; Dai, Xiaofeng; Wang, Zengyu; Zhang, Pan; Chen, Zetao (Frontiers in Energy Research, 2023)
In order to avoid safety problems caused by foreign body such as mice that may appear in the power distribution room, by demarcating the electronic fence area for key monitoring in the video surveillance screen, a foreign body intrusion monitoring and recognition approach in power distribution room based on improved yolov4 deep learning network is proposed. To optimize the detection effect, the YOLOv4 algorithm is improved from the aspects of network structure, frame detection and loss function. At the same time, the channel pruning algorithm is used to prune the model to simplify the model structure. The experimental results show the effectiveness of improved yolov4 deep learning network, which has high detection accuracy, fast detection speed, and takes up less space after pruning.